SOME CRYOGENIC WEATHERING FEATURES OF GOLD-QUARTZ VEINS AND THE FORMATION OF GOLD HALOES, BAIKAL RIFT ZONE, U.S.S.R - Taisaev T.T. (My University, 1990)
In the treeless mountains of the Baikal rift zone (U.S.S.R.), which is a very cold environment, cryogenic weathering of gold-quartz veins takes place resulting in the formation of mechanical, aqueous and biogeochemical Au haloes. The processes separating free gold from its original location within the quartz of the veins, and the redistribution of gold in the fine and coarse fractions, are controlled by two major factors: (1) the presence of fractures within quartz which form as a result of tectonic activity; and (2) the effect of water-ice transitions which provide a mechanism for moving free gold and expanding the size of the fractures. The formation of residual gold concentrations (eluvial ana alluvial placers), mechanical and stream sediment haloes, and gold-bearing silts in dammed glacial lakes, are all related to the process of separating free gold from gold ores.